Bulk Osteochondral Allograft for Osteochondral Lesions of the Talus: A Systematic Review. Issue 1 (January 2022) - Azam, Mohammad; Davey, Martin S.; Colasanti, Christopher; Mercer, Nathaniel P.; Hurley, Eoghan T.; Shimozono, Yoshiharu; Kennedy, John G.
Category: Ankle Introduction/Purpose: The use of bulk osteochondral allograft (OCA) is often warranted in patients with a large osteochondral lesion of the talus (OLT). Previous literature reported that bulk OCA has high failure and revision rates, suggesting these procedures should be thought of as an intermediate step, buying time before arthrodesis or arthroplasty is required. However, recent studies suggest that the long-term survival of bulk OCA has improved and that these procedures may provide a definitive solution for large OLT. The purpose of this study was to systematically review the literature to ascertain the outcomes of bulk OCA for OLT. Methods: Two independent reviewers performed the literature search based on PRISMA guidelines, utilizing the EMBASE, MEDLINE, and The Cochrane Library Databases. Studies were included if they reported outcomes of OLTs which were managed by bulk OCA. Results: Overall, 9 studies with 112 patients (55.4% males) including 115 ankles with a mean follow-up of 72.7 (8 - 240) months were included in this review. Pre-operative OLT characteristics showed that 68.4% were medial lesions, with a mean lesion size of 3.04cm 2 (0.7 - 6.1 cm 2 ). Overall, 23.5% of patients required revision surgery following bulk OCA; 10.4% (12/115) underwent subsequent arthrodesis, 1.7% (2/115) underwent revision osteochondral grafting and 9.6% (11/115) underwent arthroscopic debridement. Radiological outcomes reporting graft failure was 21.3% (13/61), joint space narrowing was 25.2% (29/115) and cysts were present in 19.5% (15/77) of cases. Conclusion: Patients experience satisfactory patient-reported clinical outcomes in the medium term following bulk OCA in the management of OLT. Despite recent advances in graft procurement and storage radiological graft failure and the requirement for additional surgeries still remain. At this time can only be recommended in cases that are refractory to other treatments and where the patient is aware that this may be a temporizing procedure before arthroplasty or arthrodesis.